Distribusi Penulisan Resep Obat Generik Di Rumah Sakit Kabupaten Se Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT After publishing the Indonesian Health Minister Regulation Number Per.Men.Kes. No.085/1 Januari/1989 that forces medical doctors and dentists who work in the government offices to write their prescriptions to take generical drugs, and in doing that regulation, the Indonesian Government using administrative sacntion and punish which were run from 1st July 1989. This problem is quite interesting, therefore the investigator would like to study whether the above sacntion had a significant contribution in Yogyakarta Special Region. The aim of this research is to study the influence of Per.Men.Kes No.085/1989 to medical doctors and dentists who are working in the Yogyakarta Special Region. This research is done using Descriptive Analytic Methode and data is collected using retrospective methode to take of hospital drugstore prescriptions randomly. The result shows that 3 moths before and after the Indonesian Health Minister publication, there were quite high generical prescriptions, 21% and significantly different (p